Chiral Arene Ligand as Stereocontroller for Asymmetric C−H Activation. Issue 26 (3rd May 2022) - Liang, Hao; Guo, Weicong; Li, Junxuan; Jiang, Jijun; Wang, Jun
Abstract: Development of chiral ligands is the most fundamental task in metal‐catalyzed asymmetric synthesis. In the last 60 years, various kinds of ligands have been sophisticatedly developed. However, it remains a long‐standing challenge to develop practically useful chiral η 6 ‐arene ligands, thereby seriously hampering the asymmetric synthesis promoted by arene‐metal catalysts. Herein, we report the design and synthesis of a class of readily tunable, C 2 ‐symmetric chiral arene ligands derived from [2.2]paracyclophane. Its ruthenium(II) complexes have been prepared and successfully applied in the enantioselective C−H activation to afford a series of axially chiral isoquinolones (up to 99 % yield and 96 % ee). This study not only lays chemists' longstanding doubts about whether it is possible to use chiral arene ligands to stereocontrol ruthenium(II)‐catalyzed asymmetric C−H activation, but also opens up a new avenue to achieve asymmetric C−H activation. Abstract : A class of facilely tunable, [2.2]paracyclophane‐derived chiral arene ligands has been developed, by which a ruthenium(II)‐catalyzed asymmetric C−H activation of N‐methoxybenzamides with alkynes was achieved, affording a series of axially chiral isoquinolones in up to 99 % yield with up to 96 % ee. This work opens up a new avenue to achieve asymmetric C−H activation by using a chiral arene ligand as stereocontroller.